Physicochemical and Sensory Evaluation of Ice Cream Enriched with Butterfly Pea Flower and Sorghum at Varying Levels (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The global demand for ice cream made with natural ingredients and unique flavors is rapidly increasing. However, traditional ice cream is typically low in fiber. Additionally, its high fat and sugar content contributes to obesity and related health issues, with excessive sugar intake being linked to chronic diseases like cardiovascular conditions and diabetes. Therefore, this study aimed to evaluate the physicochemical properties and sensory acceptability of ice cream formulated with butterfly pea flowers and varying percentages of sorghum incorporation. There were four different formulations with different concentrations of sorghum level, consisting of sample A (0% sorghum), sample B (0.5% sorghum), sample C (1.0% sorghum), and sample D (1.5% sorghum). Chemical properties include moisture content (64.82-65.14%), ash content (0.9702-0.9897%), crude fat content (1.584-8.268%), protein content (4.895-7.486%), fibre content (5.470-6.660%), total carbohydrates content (18.91-27.50%), and total solid contents (34.86-35.18%). The addition of sorghum enhanced the ice cream's stickiness, overrun, moisture content, ash, fibre, and total carbohydrate levels, at the p
Keywords: Butterfly pea flower; Sorghum Rice; Ice Cream; Functional food; Natural flavor